Focal segmental glomerulosclerosis after renal transplantation in a child with ANCA-associated glomerulonephritis case report and literature review - Rong, L P (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2016)
Objective: To study the clinical features and treatment of focal segmental glomerulosclerosis (FSGS) after renal transplantation in a child with ANCA-associated glomerulonephritis. Method: The clinical and pathological data of the patient treated in the Department of Pediatrics as well as in the Department of Organ Transplantation in November 2015 in the First Affiliated Hospital of Sun Yat-sen University, who was diagnosed with de novo FSGS after renal transplantation with a primary disease ANCA-associated glomerulonephritis, was analyzed retrospectively. Reports on "ANCA-associated glomerulonephritis" "(renal OR kidney) transplantation" "focal segmental glomerular sclerosis" were searched and reviewed. Result: A ten years old female was definitely diagnosed with ANCA-associated glomerulonephritis on the 81st day after the onset of primary ANCA associated glomerulonephritis. Because of progressive decline of renal function, a hemodialysis period for 7 months was administered following the pulsed methylprednisolone as well as cyclophosphamide treatment. The renal transplantation was then carried out 18 months later, the renal function recovered 7 days later while proteinuria reappeared 28 days after renal transplantation. Based on the anti-rejection treatment, 3 times pulsed methylprednisolone administration did not make difference on reducing the proteinuria and then a renal biopsy was conducted and the transplanted kidney proved to be a newly developed FSGS. Consequently, plasma exchange therapy was administrated. When the plasma exchange course finished, the proteinuria decreased significantly (from 3.270 g/24 h to 0.370 g/24 h). No reports were retrieved either in Chinese databases or at PubMed as well as Medline databases. Conclusion: FSGS appears in transplanted kidney in patient with a primary renal disease as ANCA associated glomerulonephritis with early proteinuria after transplantation as well as negative P-ANCA and MPO. Pathology of renal biopsy revealed FSGS while the pathology of other recipient was not FSGS. The patient had no response to pulsed methylprednisolone therapy. Instead, plasma exchange therapy was an alternative also effective treatment for de novo FSGS in transplanted kidney